Sword of Zen : Master Takuan and his writings on immovable wisdom and the sword Taie - Haskel, Peter (University of Hawaiʻi Press, 2013)
"Along with translations of Record of immovable wisdom and On the sword taie ..., this book includes an introduction to Takuan's distinctive approach to Zen ... It also offers an accessible overview of the actual role of the sword in Takuan's day ..."--Page 4 of cover